Sex, drugs and social connectedness: Wellbeing among HIV-positive gay and bisexual men who use party-and-play drugs - Power, J.; Mikolajczak, G.; Bourne, A.; Brown, Graham; Leonard, W.; Lyons, A.; Dowsett, G.; Lucke, J. (C S I R O Publishing, 2018)
Â© 2018 CSIRO. Background This paper explores associations between use of party-and-play drugs, including crystal methamphetamine, and wellbeing among HIV positive gay and bisexual men (GBM) in Australia. This study considers whether use of drugs in a social or sex-based setting facilitates access to social and support networks, which may in turn support wellbeing. Methods: A cross-sectional survey of Australian people living with HIV (PLHIV) was conducted. There were 714 participants (79.7%) who identified as GBM. Differences between party-and-play drug users and non-users were examined using bivariate and multinomial logistic regressions. Mediation analysis examined the indirect effect of drug use on wellbeing via social connectedness and support. Results: One in three participants (29.7%) reported party-and-play drug use within the past 12 months. Only 5% reported regular use. There were no differences between users and non-users on self-reported measures of general health, wellbeing or general social support. Compared with non-users, party-and-play drug users reported higher levels of resilience and lower levels of perceived HIV-related stigma. This was associated with spending more time with other people living with HIV and friends in the gay and lesbian community. Conclusions: While party-and-play drug use poses risks to the health of GBM, the social contexts in which these drugs are used may provide wellbeing benefits, particularly for HIV-positive GBM who may be subject to HIV-related stigma in other settings. Further research is needed to determine whether drug-use facilitates access to social networks or if people with more active social ties are more likely to engage in drug use.